(untitled) (INNOVATIVE ECONOMY, 2024)
Prokopchuk O.A. INTERNATIONALIZATION AS AN INTERDISCIPLINARY CATEGORY: EVOLUTION OF THEORETICAL CONCEPT Purpose. The aim of the article is to research the evolution of the interdisciplinary scientific category "internationalization", identification of its subject and formal specificity in various spheres of implementation. Methodology of research. The key research methods are dialectical methods of induction and deduction, analysis and synthesis, which made it possible to determine the essence of the category "internationalization", abstracting from the specifics of the sphere; and conceptual identity (forms and subjects of practical implementation) of internationalization in the economy, public administration and social sphere. Findings. It was established that "internationalization" is an interdisciplinary scientific category, the evolution of the theoretical and methodological understanding of which took place in accordance with the deepening and diversification of its practical implementation forms. Internationalization is identified as a diversified process of expanding the activities of subjects beyond national borders, by adapting the endogenous potential to the conditions of the global environment in order to gain access to new opportunities not inherent in the national space. It has been proven that the processes of internationalization in various social spheres are differentiated by forms and subjects, the priority of individual and national interests. Originality. Within the framework of a single study, the conceptual understanding of "internationalization" as an interdisciplinary scientific category was identified, and its essence was identified as a universal process that acquires specific forms, goals and priorities depending on the field of implementation. Practical value. A deep theoretical understanding of internationalization forms the basis for improving the practical mechanisms of its implementation at the local and national levels. Key words: internationalization, scientific category, conceptual essence, definition, public administration, education, business internationalization.